Construction of a cloud-based mold manufacturing system based on JAFMAS. (November 2020) - Zhang, Peipei; Wang, Dongsheng; Zhang, Junhui
Abstract: Molds are the basis of manufacturing of other products, and thus have higher requirements and more complex design processes than other products. Therefore, studying the technologies used in mold production is necessary. This paper aims to build a cloud manufacturing system of mold manufacturing enterprises based on the Java-based agent framework for multi-agent systems (JAFMAS). Specifically, according to the operation characteristics of different cloud-based manufacturing enterprises, this paper first made in-depth analysis of the cloud manufacturing and multi-agent technology, and put forward a hierarchical model of cloud manufacturing system based on multiple agents. Then, as per the structure of the agents and JAFMAS, the interaction and collaboration mechanism between agents in the system were analyzed to establish the functions of the cloud-based mold manufacturing system, thereby building a cloud-based manufacturing system for mold manufacturers based on JAFMAS.